2015
DOI: 10.1111/bju.13308
|View full text |Cite
|
Sign up to set email alerts
|

Active surveillance in localized prostate cancer: comparison of incidental tumours (T1a/b) and tumours diagnosed by core needle biopsy (T1c/T2a): results from the HAROW study

Abstract: ObjectiveTo conduct a comparative prospective analysis of patients with incidental T1a/T1b prostate cancer (IPCa) and those with prostate cancer (PCa) diagnosed by core needle biopsy, treated by active surveillance (AS), with regard to inclusion criteria, progression and switch to deferred treatment. Patients and MethodsThe HAROW study is an observational outcomes research study on the management of localized PCa. Treating urologists reported clinical variables and information on therapy and clinical course of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
3
7
1
Order By: Relevance
“…This is also comparable to other large trials. 15 Hence, our findings support the implementation of incidental tumours in AS, as it is recommended in the recently published S3-Guidelines of the German Society of Urology. 16 Dropout and compliance Only few reports have looked at compliance problems in AS.…”
Section: Discussionsupporting
confidence: 81%
“…This is also comparable to other large trials. 15 Hence, our findings support the implementation of incidental tumours in AS, as it is recommended in the recently published S3-Guidelines of the German Society of Urology. 16 Dropout and compliance Only few reports have looked at compliance problems in AS.…”
Section: Discussionsupporting
confidence: 81%
“…Our results reiterate findings from other studies that were conducted over shorter durations and at least five years after our study had begun, including PRIAS (2006), HAROW (2008–2013), and The Movember Foundation’s GAP3 cohort (2014–2016; a database to which we have also contributed) [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Discussionsupporting
confidence: 88%
“…Here, we prospectively assessed our T1a/b and T1c subgroups with respect to their reclassification rates, which occurred approximately thrice as quickly in the T1c group (reclassification per 3.6 years) versus the T1a/b group (reclassification per 11.2 years). One other study has reported similarly, noting a doubled reclassification rate after biopsy in T1c patients, though its mean FU time was only 2.4 years [ 15 ]. Moreover, the delayed reclassification rate in our T1a/b cohort indicates that such patients (a) live longer prior to developing a definitive treatment requirement, and (b) may be better candidates for WW than definitive active treatment.…”
Section: Discussionmentioning
confidence: 96%
“…Compared to the termination rate on AS in 14–41% of patients by prostate biopsy, those in incidental prostate cancer patients of 11–19% are likely lower. 28 , 29 In the present study, no significant differences were observed in the termination rates on AS (48.7% vs. 61.4%; P > 0.99) according to diagnostic methods. However, patients with incidental prostate cancer had longer AS adherence duration and follow-up duration.…”
Section: Discussioncontrasting
confidence: 67%